New combinations in Agave (Asparagaceae): A. amica, A. nanchititlensis, and A. quilae - Thiede, Joachim; Govaerts, Rafaël (Phytotaxa, 2017)
Phylogenetic studies of Agave Linnaeus (1753: 323) and related genera (Asparagaceae, Agavoideae) thus far published were based either on molecular (Bogler & Simpson 1996; Bogler et al. 2006; Good-Ávila et al. 2006; Scheinvar et al. 2017) or on morphological data (Hernández-Sandoval 1995; Tambutti in Eguiarte et al. 2006). Most studies showed that the genera Manfreda Salisbury (1866: 78), Polianthes Linnaeus (1753: 316) and Prochnyanthes Watson (1887: 457) are nested within the large genus Agave, thus rendering Agave as traditionally circumscribed (= Agave s.str.) paraphyletic. The sole study in which Manfreda, Polianthes and Prochnyanthes grouped separate from and not nested within Agave is the molecular AFLP study of Gil-Vega et al. (2007).